1987
DOI: 10.3758/bf03204874
|View full text |Cite
|
Sign up to set email alerts
|

Cortical dynamics of three-dimensional form, color, and brightness perception: I. Monocular theory

Abstract: A real-time visual processing theory is developed to explain how three-dimensional form, color, and brightness percepts are coherently synthesized. The theory describes how several fundamental uncertainty principles which limit the computation of visual information at individual processing stages are resolved through parallel and hierarchical interactions among several processing stages. The theory hereby provides a unified analysis and many predictions of data about stereopsis, binocular rivalry, hyperacuity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
155
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 225 publications
(163 citation statements)
references
References 126 publications
5
155
0
Order By: Relevance
“…Thus, in these conditions observers see the spread of subjective color without seeing a distinct subjective contour, suggesting that color spread and the formation of a subjective contour are governed by separate mechanisms. This is parallel to findings which show that color spread and contour formation in the static neon color display are governed by separate mechanisms (Grossberg andMingolla 1985a, 1985b;Grossberg 1987;Watanabe and Sato 1989). For conditions with test and surround dots of the same chromaticity (both red or both green) and of different luminances, color spread was perceived if the test dots were more luminous than the surround dots but not when the test dots were less luminous than the surround dots (figure 4, bottom two panels).…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Thus, in these conditions observers see the spread of subjective color without seeing a distinct subjective contour, suggesting that color spread and the formation of a subjective contour are governed by separate mechanisms. This is parallel to findings which show that color spread and contour formation in the static neon color display are governed by separate mechanisms (Grossberg andMingolla 1985a, 1985b;Grossberg 1987;Watanabe and Sato 1989). For conditions with test and surround dots of the same chromaticity (both red or both green) and of different luminances, color spread was perceived if the test dots were more luminous than the surround dots but not when the test dots were less luminous than the surround dots (figure 4, bottom two panels).…”
Section: Resultssupporting
confidence: 70%
“…Redies and Spillmann (1981) showed that the spread of neon color occurs in the static display even at equiluminance, as was confirmed experimentally by Ejima et al (1984). Grossberg andMingolla 1985a, 1985b;Grossberg 1987) proposed a model in which two separate mechanisms are postulated, one to produce color spreading and the other to produce the subjective contour. In line with this model, the experiments of Watanabe and Sato (1989) showed that the neon color effect is seen without a subjective contour when the inner and outer segments are near equiluminance, suggesting that the perception of color spreading and the formation of a subjective contour are governed by two different mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…A horizontal bipole cell is also inhibited by activation of vertical hypercomplex cells ( Figure 13A). This spatial impenetrability operation (Grossberg, 1987a;Grossberg & Mingolla, 1987) prevents collinear grouping from occurring across regions wherein noncollinear orientations are present.…”
Section: A Monocular Boundary Contour System Model Of Cortical Boundamentioning
confidence: 99%
“…In other words, end-cuts were not introduced in the model to explain boundary detachment. They were introduced to explain how the visual system compensates for measurement uncertainties that are caused by using oriented receptive fields, a much more basic requirement (Grossberg, 1987a;Grossberg & Mingolla, 1985b).…”
Section: Neon Color Spreadingmentioning
confidence: 99%
“…Grossberg and Mingolla (Grossberg, 1987; Gossberg & Mingolla, 1985a, 1985b have, in fact, constructed a model in which the mechanism for the color spreading is different from that for the illusory contour formation.…”
mentioning
confidence: 99%